Secondary school students' habits of using note-taking strategies - BENZER, AHMET (My University, 2022)
Abstract. Note-taking is summarizing what one has understood in one's own words to remember it later. Notetaking is one of the most important writing activities in passing the information acquired through listening from temporary memory to permanent memory. In this study, 5 different strategy training were given to 7th -grade students for 6 weeks. After the training on each strategy was given to the students, they were expected to apply the relevant note-taking strategies after the listening texts. Multiple cases and holistic multiple case design, which is one of the case study types, were used in the research. The note-taking papers of the students were evaluated according to the criteria of the strategies. Student opinions were coded by subjecting content analysis and the findings were interpreted. As a result of the study, it was determined based on the student interview forms that before the notetaking training was given, the students could not take notes because they had difficulty in distinguishing between necessary and unnecessary information and that in the Cornell strategy, students had difficulty in identifying key words while listening. It was seen that the students were most successful in a mind map and chart strategies out of the 5 strategies, and the students were limited in applying the outline strategies. In all of the strategies, it was seen that the students were able to apply the stages of identifying keywords and creating short sentences. As a result of the research, when note-taking strategies were taught, students were successful in identifying keywords, expressing them in short sentences, and connecting information; it has been concluded that when education is not given, they tend not to take notes or to take notes on a single sentence. Based on these results, it has been suggested in line with the data obtained from the findings that note-taking strategies training should be included in the textbooks, that each strategy should be applied after texts with appropriate content, and which strategies should be applied before, during and after listening/reading.
Keywords: Cornell note-taking method; mind map; flow-based note-taking; outlines; charting; note-taking strategies